2017
DOI: 10.1016/j.apt.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Levitation-jet synthesis of In-O nanoparticles with room-temperature ferromagnetic properties

Abstract: Octahedral and roughly spherical In-In 2 O 3 nanoparticles ranging in average particle size from 30 up to 300 nm were prepared by levitation-jet aerosol synthesis through condensation of metal indium vapor in helium gas flow with gaseous oxygen/air injection at ambient and reduced pressure. Scanning electron microscopy (SEM), X-ray diffraction (XRD), BET measurements, UV-vis, FT-IR, Raman, XPS, and vibratingsample magnetometry (VSM) characterized the nanoparticles. Room-temperature ferromagnetism with maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…Such molecules are splitting over the defects on the surfaces of the growing MgO nanoparticles, thus stimulating the most surface-defective incipient spherical shapes [32] and effect on the RTFM evolution [35]. We suggested that such behavior takes place during some manipulations of the levitation-jet synthesis conditions when an excess amount of the oxidizer gas was presented in the basic gas flow [30]. For the used combined mode, initial oxidation of NPs was uncompleted, because of secondary character of this process compared with the primary process of vapor metal condensation and hence a postcondensation intensification of the oxidation process might take place [32].…”
Section: Characterization Of Npsmentioning
confidence: 97%
See 1 more Smart Citation
“…Such molecules are splitting over the defects on the surfaces of the growing MgO nanoparticles, thus stimulating the most surface-defective incipient spherical shapes [32] and effect on the RTFM evolution [35]. We suggested that such behavior takes place during some manipulations of the levitation-jet synthesis conditions when an excess amount of the oxidizer gas was presented in the basic gas flow [30]. For the used combined mode, initial oxidation of NPs was uncompleted, because of secondary character of this process compared with the primary process of vapor metal condensation and hence a postcondensation intensification of the oxidation process might take place [32].…”
Section: Characterization Of Npsmentioning
confidence: 97%
“…Mg-O nanoparticles were obtained by using the Gen's levitation-jet generator described in details elsewhere [29,30], which was modified for the special goals of this research ( Figure 1).…”
Section: Synthesis Of Npsmentioning
confidence: 99%
“…Figure shows that all BITO: x Eu samples have only one wide peak in the range of 400–1000 cm –1 due to the vibrations of the metal oxygen bond. The previous literature reported that the Ba–O–Ba and Ba–O bonds’ stretching vibrations are 692 and 856 cm –1 , respectively; the stretching vibrations of In–O bonds are 557–566 cm –1 , whereas the bending vibrations are 600–607 cm –1 . The Ta–O–Ta and Ta–O bonds’ stretching vibrations appear between 450 and 1000 cm –1 . , The stretching vibrations of Eu–O bonds mainly appear at 616 cm –1 .…”
Section: Resultsmentioning
confidence: 87%
“…Subsequently, the strongest characteristic peaks of Ba, In, Ta, O, and Eu were narrowly scanned, which are shown in Figure b–f. The HR-XPS spectrum of Ba is composed of two main peaks at 779.3 and 794.6 eV in Figure b, corresponding to the Ba 3d 5/2 and 3d 3/2 , respectively. , In Figure c, the two strong peaks at around 444.1 and 451.7 eV correspond to In 3d 5/2 and In 3d 3/2 , which are due to the In 3+ . , The peaks that were observed at 25.4 and 27.4 eV in Figure d can be assigned to the binding energies of Ta 4f 7/2 and 4f 5/2 , respectively. , In the high-resolution XPS spectra of Eu 3d, the characteristic peaks of Eu 3+ and Eu 2+ were observed. The four peaks at 1134.3, 1163.2, 1123.7, and 1152.9 eV were obtained by XPSPEAK4.1 software fitting, corresponding to the binding energy of 3d 5/2 and 3d 3/2 of Eu 3+ and Eu 2+ , ,, and the ratio of the peak area of Eu 3+ /Eu 2+ was 2:1.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation